Effect of hyaluronidase on tissue‐engineered human septal cartilage. (13th June 2016) - Watson, Deborah; Reuther, Marsha S.; Wong, Van W.; Sah, Robert L.; Masuda, Koichi; Briggs, Kristen K.
Abstract : Objectives: Structural properties of tissue‐engineered cartilage can be optimized by altering its collagen to sulfated glycosaminoglycan (sGAG) ratio with hyaluronidase. The objective was to determine if treatment of neocartilage constructs with hyaluronidase leads to increased collagen:sGAG ratios, as seen in native tissue, and improved tensile properties. Study Design: Prospective, basic science. Methods: Engineered human septal cartilage from 12 patients was treated with hyaluronidase prior to culture. Control and treated constructs were analyzed at 3, 6, or 9 weeks for their biochemical, biomechanical, and histological properties. Results: Levels of sGAG were significantly reduced in treated constructs when compared with control constructs at 3, 6, and 9 weeks. Treated constructs had higher collagen:sGAG ratios when compared with control constructs at 3, 6, and 9 weeks. Treated constructs had greater tensile strength, strain at failure, and increased stiffness as measured by the equilibrium and ramp tensile moduli when compared with the untreated control constructs. Continued time in culture improved tensile strength in both treated and control constructs. Conclusion: Hyaluronidase treatment of engineered septal cartilage decreased total sGAG content without inhibiting expansive growth of the constructs. Decreased sGAG in treated constructs resulted in increased collagen to sGAG ratios and was associated with an increase in tensile strength and stiffness. With additional culture time, sGAG increased modestly in depleted constructs, and some initial gains in tensile properties were dampened. Alterations in the dosage of hyalurondiase during neocartilage fabrication can create constructs that have improved biomechanical properties for eventual surgical implantation. Level of Evidence: NA. Laryngoscope, 126:1984–1989, 2016